2018
DOI: 10.1371/journal.pone.0204168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human sepsis on CCCTC-binding factor associated monocyte transcriptional response of Major Histocompatibility Complex II components

Abstract: BackgroundAntigen presentation on monocyte surface to T-cells by Major Histocompatibility Complex, Class II (MHC-II) molecules is fundamental for pathogen recognition and efficient host response. Accordingly, loss of Major Histocompatibility Complex, Class II, DR (HLA-DR) surface expression indicates impaired monocyte functionality in patients suffering from sepsis-induced immunosuppression. Besides the impact of Class II Major Histocompatibility Complex Transactivator (CIITA) on MHC-II gene expression, X box-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 58 publications
6
13
0
Order By: Relevance
“…Recently, we could demonstrate in circulating monocytes of patients with sepsis, that an increased CTCF-occupancy at this intergenic region is associated with selective changes in adjacent HLA-gene expression. These findings indicate a CTCF mediated enhancer blockade as a potential mechanism contributing to an immunocompromised phenotype [18].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Recently, we could demonstrate in circulating monocytes of patients with sepsis, that an increased CTCF-occupancy at this intergenic region is associated with selective changes in adjacent HLA-gene expression. These findings indicate a CTCF mediated enhancer blockade as a potential mechanism contributing to an immunocompromised phenotype [18].…”
Section: Introductionmentioning
confidence: 71%
“…The impact of CTCF on global gene expression has been investigated in numerous cell types including those of the innate immune system [23]; however, its role in the transcriptional regulation of antigen presentation during postoperative human sepsis has not been elucidated so far. Based on previous work hinting towards a CTCF-mediated enhancer blockade of selected HLA genes during critical illness [18], we analysed global CTCF occupancy within the MHC-II in patients suffering from postoperative abdominal sepsis. Compared to a matched control cohort, we could demonstrate that postoperative sepsis was associated with a selective and persistent increase in CTCF enrichment at binding sites located next to classical HLA genes that code for proteins expressed on the surface of antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduction compounded with the already reduced number of myeloid cells leading to ~100 fold reduction in MHC II-expressing cells in CLP hosts ( Figure 1—figure supplement 3g,i ). Prior studies have demonstrated alterations in MHC expression by myeloid cells which are dysregulated following sepsis ( Jensen et al, 2020 ; Monneret et al, 2006 ; Siegler et al, 2018 ). MHC II expression is not only a marker of activation of these cell populations but also serves to present antigen to CD4 T cells, including autoreactive T cells that are critical mediators of disease in EAE.…”
Section: Resultsmentioning
confidence: 99%